Inovasi Pembelajaran SMA/MAN Guru dalam Merancang Kurikulum Selama Pandemi Covid-19 di Kecamatan Dolok Batu Nanggar - Afidah Nadiah Lubis (Education & Learning, 2022)
This study uses descriptive qualitative research methods by analyzing a case study regarding online learning innovations at SMA Negeri 1 Dolok Batu and MA Al-Washliyah Serbelawan during the Covid-19 pandemic. Teachers at SMA Negeri 1 Dolok Batu use online learning following the protocol from the government and innovate in learning to make it better during the teaching and learning process.